Pengaruh Teknik Pembelajaran Ice Breaking Terhadap Hasil Belajar PKn pada Kelas 5 di Negeri 14 Rambang - Lestari, Dika; Junaidi, Ilham Arvan; Adrianus, Dedy (Indonesian Research Journal on Education, 2023)
The formulation of the problem in this study is whether there is an effect of ice breaking learningtechniques on PKN learning outcomes in grade 5 at SD Negeri 14 Rambang. The purpose of thisstudy was to determine whether or not there was an influence of ice breaking learning techniqueson the learning outcomes of PKN in grade 5 at SD Negeri 14 Rambang. The method used in thisresearch is quantitative with a design design that is one group pretest-posttest. The researchsample is all 5th graders, totaling 26 students. The results of this study indicate that PKN learningoutcomes have increased with the use of ice breaking learning techniques. This is evidenced in the results of the t-test calculation with a significant level (α) t = n – 1 = 25. The results obtained are tcount = 9.49 and ttable = 2.056. Thus it can be concluded that tcount > ttable or 9.49 > 2.056, then Ho is rejected and Ha is accepted. This means that the hypothesis states that the use of ice breaking learning techniques affects the learning outcomes of 5th grade PKN students at SD Negeri 14 Rambang.